Tracking and quantifying spatter characteristics in a laser directed energy deposition process using Kalman filter. (September 2022) - Sikandar Iquebal, Ashif; Yadav, Aakash; Botcha, Bhaskar; Krishna Gorthi, Rama; Bukkapatnam, Satish
Abstract: Laser-based directed energy deposition (L-DED) has emerged as one of the most promising additive manufacturing (AM) technologies in the past decade. This is particularly due to its ability to print functionally graded materials and achieve a higher deposition rate compared to its counterparts. For L-DED, the flow dynamics of the powder particles and laser-material interactions are the chief determinants of the build quality. In particular, we are interested in the characterization of spatter, which is the ejection of the molten material from the deposition zone that includes the melt pool and the area where the laser interacts with the incident powder particles. Spatters are detrimental to the overall build quality as they can increase porosity and lead to irregular surface morphology. While recent studies have investigated the spatter formation, very little attention has been given to its quantitative in situ characterization. To this end, we develop a high-speed imaging capability integrated with an L-DED process to record the trajectory of the spatter particles as they eject out from the deposition zone. We use a Kalman filter to track the trajectory of the individual spatter particles in real-time. By using the trajectory information and apriori knowledge of the material properties, we estimate the percentage of the material lost as spatter. Our results indicate that at a laser power of 300 W and a feed rate of 7.41 mm/sec, only an estimated 11% of the powder material (released from the nozzles) interacts with the laser beam. Out of this, approximately 12% of the material is ejected out as spatter. This shows that a significant portion of the material is wasted during the L-DED process.